Proposal of analysis method to reduce back-flashover rate taking account of tower footing resistance - Yusreni Warmi; Zulkarnaini Zulkarnaini; Abdul Rajab; Chitra Yuanisa; Rizki Oktrinanda Elyas; Andi M. Nur Putra; Zuriman Anthony (Institute of Advanced Engineering and Science, 2023)
The number of lightning stroke on the tower of the 150 kV Koto Panjang-Payakumbuh transmission line located the rocky area has been observed. The high value of tower footing resistance indicates the occurrence of the back-flashover in the transmission line at intensity of 74%. The back-flashover occurrence is dominantly triggered by the tower footing resistance value. Also, the rate of back-flashover has an effect on the value of the tower footing resistance by considering the number of electrode installations. A design is proposed for the grounding system of the tower footings in order to reduce the rate of back-flashover. The results presenting in numerical simulation indicates that it works properly after adding 4 electrodes. That is to say, installing 4 electrodes in each tower has successfully decreased the tower footing resistance value, back-flashovers rate 80% and 90-95% of present value respectively. The insulator voltage can be reduced to less than half of the present voltages as much as 30-50%. In more detail, in tower 77, the value of the tower footing resistance drops to 2.84 Ω, the flashover rate drops to 0.57/100 km/year and the insulator voltage drops to 0.99 MV when a disturbance occurs.